WHAT INFLUENCES ONLINE TRANSPORTATION CUSTOMERS TO BE SATISFIED IN THE NEW NORMAL? - Mohammad Annas; Humairoh Humairoh; Agung Budi (Dynamic Management Journal, 2023)
This observation targets to research the effect of service quality and website quality on Gojek online transportation provider purchasers’ happiness in the new normal. The approach used in this have a look at is causal studies. The sample included 100 Gojek internet users from Tangerang town, Banten Province. Purposive sampling was utilized in this examination. Statistics were retrieved using a questionnaire instrument and processed using the Scala Likert Summated score (LSR) approach with a 1 - 5 scale. SPSS version 25 was used for information evaluation techniques. With a t count of 6.286, the outcomes found a positive and significant effect of website quality characteristics on personal satisfaction. With a t remember of 0.811, there was no positive and significant influence on service quality traits on user satisfaction. Simultaneously, facts processing findings discovered that website and service impacted customer happiness, measured by the computed F value of 59.298. R2 of 0.550 indicates that service quality and website can best explain 55.0% of consumer satisfaction factors. user satisfaction regression equation = 0.886+0.083 service quality+0.698 website quality+e.